2007
DOI: 10.1111/j.1349-7006.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection‐negative gastric cancer in Japanese hospital patients: Incidence and pathological characteristics

Abstract: We used Helicobacter pylori sero-positivity and mucosal atrophy as detected by the serum pepsinogen method to identify H. pylori infection-negative gastric cancer patients with or without atrophy. One hundred and six of 748 (14.2%) primary gastric cancer patients were infection-negative by a serum antibody detection system. Further, 121 (16.2%) of the 748 were negative for gastric mucosal atrophy by the pepsinogen method, of whom 15/748 (2.0%) were H. pylori-negative by pepsinogen I level (> > > >70 ng/mL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
107
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 25 publications
(46 reference statements)
3
107
2
Order By: Relevance
“…H. pylori positivity in the general population as well in gastric cancer patients is very high in Japan and in countries with a high incidence of gastric cancer. [19][20][21]29 It is interesting to note that in gastric cancer patients, very low positivity rates of H. pylori infection have been reported from the US, [30][31][32][33] and clinical studies demonstrated clearly lower survival rates when compared with Japanese patients at the same stages of disease. 34 Differences in prognosis between Eastern and Western series have been explained on the basis of different surgical approaches, less advanced stage of disease, and more careful tumor staging 35 ; the association with H. pylori status may shed more light on geographic variability in the prognosis of patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori positivity in the general population as well in gastric cancer patients is very high in Japan and in countries with a high incidence of gastric cancer. [19][20][21]29 It is interesting to note that in gastric cancer patients, very low positivity rates of H. pylori infection have been reported from the US, [30][31][32][33] and clinical studies demonstrated clearly lower survival rates when compared with Japanese patients at the same stages of disease. 34 Differences in prognosis between Eastern and Western series have been explained on the basis of different surgical approaches, less advanced stage of disease, and more careful tumor staging 35 ; the association with H. pylori status may shed more light on geographic variability in the prognosis of patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, very high infection rates also have been reported from Japan, and negative H. pylori status in Japanese gastric cancer patients has been recently estimated to range from between 2% and 11%. 20 It is well known that the prevalence of H. pylori infection in the general population is higher in countries with a higher incidence of gastric cancer 21 ; in Tuscany, the incidence of gastric cancer is very high compared with other regions of Italy. 22 Epidemiologic factors and the sensitivity of the methods used could explain the high rates of H. pylori positivity reported in the current series.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the accuracy of determining HP-status, some studies have referred to the incidence using only histopathology [14] or only anti-HP antibodies and the pepsinogen method [15], one determined it using anti-HP antibodies and histopathology, endoscopic findings, the pepsinogen method, and the urea breath test or the rapid urease test [3], and yet another determined it on the basis of histopathology, the rapid urease test, anti-HP antibodies, and a history of eradication therapy [16]. In contrast, we used six criteria [urea breath test results (negative), endoscopic findings, histopathology, pepsinogen test results, presence of anti-HP antibodies, and history of eradication therapy] in our study to select HP-patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the incidence of gastric cancer in patients seronegative for H. pylori was 2 12 , compared with 0.66 in those without H. pylori infection 13 . This difference is likely due to the inclusion of current or previous H. pylori-infected subjects with negative serological test results.…”
Section: Discussionmentioning
confidence: 99%